2019
DOI: 10.29089/2019.19.00092
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the menstrual cycle on the muscle strength in young women

Abstract: Introduction: Nowadays more women are trying to shape their figure properly. Changes in the menstrual cycle can affect the dynamic muscle parameters of women. Aim: The aim of the study was to assess muscle strength in various phases of the menstrual cycle in young women Material and methods: The study involved 23 women aged 20–22. All the women had menstrual periods (27 ± 3.16 days). The strength measurement was made by means of Microfet2 (Hoggan Health Industries, USA), which was fixed permanently to the fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
1
0
Order By: Relevance
“…There are contradictions in the scientific literature since increases in muscle strength in the FP and a decrease in fatigue have been reported [21], while other studies have not reported significant differences in muscle strength values between the different phases of the MC [22,23]. In the case of aerobic or anaerobic training, there is no evidence that performance fluctuates over the duration of the MC [24].…”
Section: Introductionmentioning
confidence: 96%
“…There are contradictions in the scientific literature since increases in muscle strength in the FP and a decrease in fatigue have been reported [21], while other studies have not reported significant differences in muscle strength values between the different phases of the MC [22,23]. In the case of aerobic or anaerobic training, there is no evidence that performance fluctuates over the duration of the MC [24].…”
Section: Introductionmentioning
confidence: 96%
“…However, the effect of sex steroids on function of the musculoskeletal system in women, especially their passive parts, has not been fully explored yet, with the results of certain examinations being contradictory [ 14 , 15 , 16 , 17 ]. This issue is very important because a significant decrease in strength is associated with risky biomechanical strategies that may predispose to injury [ 16 ].…”
Section: Introductionmentioning
confidence: 99%